99.3k views
5 votes
If anyone can help ??

If anyone can help ??-example-1

1 Answer

7 votes

Consider expanding the right hand side as


y=\sqrt[3]{(x(x-2))/(x^2+1)}=x^(1/3)(x-2)^(1/3)(x^2+1)^(-1/3)

Then taking the logarithm of both sides and applying some properties of the logarithm, you have


\ln y=\frac13\ln x+\frac13\ln(x-2)-\frac13\ln(x^2+1)

Now differentiate both sides with respect to
x:


\frac1y(\mathrm dy)/(\mathrm dx)=\frac1{3x}+\frac1{3(x-2)}-(2x)/(3(x^2+1))=\frac23(x^2+x-1)/(x(x-2)(x^2+1))


(\mathrm dy)/(\mathrm dx)=\frac23(x^2+x-1)/(x(x-2)(x^2+1))y


(\mathrm dy)/(\mathrm dx)=\frac23(x^2+x-1)/(x(x-2)(x^2+1))\sqrt[3]{(x(x-2))/(x^2+1)}

User Keshaw
by
5.4k points